Strength training recommendations for developmental Rugby Sevens athletes - Harrison, S. (Journal of Australian Strength and Conditioning, 2018)
A review of physical demands within Rugby Sevens matches, as well as physical qualities of elite players was conducted, which highlighted the importance of developing capacities such as strength, power, speed and endurance for elite performance. Methods of physical preparation have been outlined for elite players, however, for the developmental athlete, strength and conditioning coaches must take a more individual approach to athletic performance. This method should involve assessment of athlete`s strengths and weaknesses to provide tailored exercise progressions that target key movement streams applicable to rugby sevens performance. Appropriate periodization of training loads is also important to ensure that athletes are progressing to more advanced movements but also developing greater strength and power capacities, without leading to accumulated fatigue or injury.